Single incision laparoscopic appendectomy with surgical-glove port is cost-effective and reliable in complicated acute appendicitis: A casecontrol multicenter study in Colombia - Andrés Felipe Carrillo Montenegro; Sofía Aristizabal Rojas; Jean André Pulido Segura; Mauricio Pedraza; Laura Padilla; Ivan David Lozada-Martinez; Alexis Rafael Narvaez-Rojas; Luis Felipe Cabrera-Vargas (Heliyon, 2023)
Background: The single-port (SPL) and multi-port (MPL) laparoscopic approach are the gold standard of management of acute appendicitis, due to its multiple advantages over open surgery, mainly because of its direct effects on recovery, esthetics and costs of the procedure. However, in third-world countries, the laparoscopic approach is not yet fully reproducible due to the costs of the technique. The surgical-glove port single incision laparoscopic appendectomy (SGP-SILA) has been proposed as a viable option. However, it has never been studied in Colombia. Objective: To evaluate the cost-effectiveness and reliability of SGP-SILA in the management of complicated acute appendicitis, compared to traditional MPL approach. Materials and methods: A retrospective case control study was carried out comparing patients undergoing laparoscopic appendectomy by SGP-SILA vs. MPL, evaluating operating costs associated with intraoperative and postoperative variables in two tertiary centers in Bogota, Colombia. The data were analyzed and expressed according to their nature and distribution. Results: 116 patients were included (SGP-SILA: 62 and MPL: 54). The median surgical time for SGP-SILA was 60 min vs. 39 min for MPL. SGP-SILA was shown to cause lower frequency of surgical site infection (4 vs. 8 patients; p = 0.047). It was found a significant correlation between Grade III surgical site infection and surgery time (p = 0.047) in the MPL group; also, with hospital stay (p < 0.001). Also, a lower risk of surgical site infection was found with the SGP-SILA technique (22% vs. 31%). SGP-SILA generated a reduction in both direct and indirect operating costs of approximately 10% (616 USD vs. 683 USD). Conclusion: SGP-SILA and MPL are feasible and comparable procedures in the resolution of complicated acute appendicitis. SGP-SILA turns out to be more cost-effective compared to MPL, due to the use of more easily accessible instruments. This may be a reproducible technique in low- and middle-income countries.